(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2015)
The current legal framework in the UK governing deceased organ donation has adopted the doctrine of consent as its central guiding principle. Under the Human Tissue Act 2004, appropriate consent must be given for the removal of organs from a cadaver to be lawful. However, this position requires justification; consent is not a free-standing principle, but must exist in relation to a potential right violation. In healthcare, the need for consent has been grounded on the protection of the patient’s rights to autonomy and bodily integrity. These rights are not present in the context of deceased organ donation, and therefore consent should not be required. Instead, we should adopt a system of routine retrieval with opt-out based on the best interests of the donor. This recognises the fact that both the deceased and their relatives can have strong interests regarding the use of the body after death, which, although not sufficient to ground a right, must be taken into consideration. A system of routine retrieval with opt-out would also result in more organs for potential recipients, and reduce the decision-making burden on families.